Differences in Manifestation of Adaptability in international students - A I Krupnov; A V Sheptura (Peoples' Friendship University of Russia (RUDN University), 2014)
The article describes the peculiarities and the differences in the manifestation of adaptability in African, Chinese and Latin American students studying in Russian University.